Bibliometric Analysis with VOSviewer on Workplace Diversity and Its Implications for Organizational Practices - Wibisono, Yohanes; Sopiah, Sopiah; Zagladi, Arief Noviarakhman (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
This study applies a bibliometric approach to evaluate publication trends related to "Workplace Diversity and Its Implications for Organizational Practices" in Scopus-indexed scientific journals from 2020 to 2024. The increasing urgency to address workplace diversity stems from globalization, evolving workforce demographics, and the growing demand for equitable and inclusive organizational practices. Diversity management is critical for enhancing innovation, improving employee well-being, and addressing social equity challenges in both developed and developing nations. Utilizing the VOSviewer software, this study analyzes publication patterns, author affiliations, and keyword distributions associated with workplace diversity topics. From the 60 articles reviewed, findings indicate that interest in workplace diversity fluctuated, with the highest number of publications recorded in 2024. The results also reveal that the United States is the largest contributor to publications on this topic, followed by India and the United Kingdom. Network visualization analysis highlights key terms such as "Diversity," "Workplace Diversity," and "Inclusion," underscoring diversity’s pivotal role in enhancing inclusion and driving organizational performance. This study provides insights into publication trends and identifies potential areas for future research in workplace diversity and its implications for organizational practices.